Partitioning and Chemical Environments of Minor Elements in Individual Large Benthic Foraminifera Cultured in Temperature-Controlled Tanks - Yoshimura, Toshihiro; Maeda, Ayumi; Tamenori, Yusuke; Suzuki, Atsushi; Fujita, Kazuhiko; Kawahata, Hodaka (Frontiers in Earth Science, 2019)
Because reef-dwelling large benthic foraminifera (LBF) tests, which is composed of high-magnesium calcite, are the common components of modern reef sediments, and ancient reef carbonate rocks, they can provide a continuous record of the paleoenvironment of reef sediments. Evaluation of the responses of the minor element concentrations (Mg, Sr, Na, P, and S) of individual tests to ambient temperature and LBF growth modes was conducted with two cultured species, Calcarina gaudichaudii and Amphisorus kudakajimensis. The elements were assessed as tracers of temperature, salinity, nutrient concentration, and calcification rate. The Mg content of C. gaudichaudii and the Sr content of both species were controlled by temperature. It can be confirmed that the Mg of individual tests of C. gaudichaudii is a useful paleothermometer. There was a large biological modulation of Na, P, and S incorporation. In-situ XANES analysis revealed that both inorganic and organic species contributed to the P and S content of LBF tests. We observed five sulfur components with variable oxidation states.